Use of a simple, inexpensive device for collection of blood during acute normovolaemic haemodilution in a Jehovah's Witness patient. Issue 2 (28th October 2015) - Dunseth, C.; Collins, L.; Reddy, S.; Schlueter, A. J.
Abstract : Postoperative anaemia is a concern for patients who refuse blood products or have rare blood types. Acute normovolaemic haemodilution (ANH) is a potential solution for these challenging populations. However, protocols for ANH provide limited detail on preparation of blood collection systems. This report describes a novel protocol for ANH and an example of a patient who clearly benefited from ANH.